Fodor's 2009 Alaska. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to Alaska, with maps and information on hotels and restaurants, shopping and entertainment, and other interesting sites.
"Pullout map inside"--Cover.
Spine title: Fodor's Alaska 2009.
Includes bibliographical references (p. [503]), filmography (p. [503]-504) and index.
Young Adult
Keywords: Alaska -- Guidebooks; Alaska -- Guidebooks